Pengaruh Return On Investment Earning Per Share Dan Dividen Per Share Terhadap Harga Saham Perusahaan Manufaktur Di Bursa Efek Indonesia 2012-2015 - Elisa Eka Chintyawati dan Wahyu Murti (Jurnal Manajemen FE-UB, 2016)
This study aims to determine the effect of the return on investment, earning per share and dividend per share either partially or simultaneously at Indeks Stock Exchange 2012-2015.  Total population in the study is a quantitative method. The sampling technique using panel data. The variable in this study is the independent variable (independent) consisting of return on investment, earning per share and dividend per share and the dependent variable (dependent) is Indeks Stock Exchange.The results showed that the return on investment, earning per share and dividend per share effecting significant partially on Indeks Stock Exchange. return on investment, earning per share and dividend per share and Indeks Stock Exchange, effecting significant Simultaneously, return on investment, earning per share and dividend per share and Indeks Stock Exchange effecting significant effect on Indeks Stock Exchange level determination coefficient to 75,22%. Key words: Return on Investment (ROI), Earning per Share (EPS) , Dividen per Share (DPS and Indeks Stock Exchange